Pengaruh citra merek, kepercayaan merek, dan kepuasan pelanggan terhadap loyalitas merek sepatu NIKE di Surabaya - Rollaz Dodo Pamungkas (Journal of Business & Banking, 2019)
This study aimed to test the effect of the brand image, brand trust, and customer satisfaction on brand loyalty NIKE shoes in Surabaya. This quantitative study used SPSS version 16.00 for the data analysis, with the population of Nike shoes in Surabaya. The data were collected using questionnaires towards 80 respondents. They were selected based on the method of purposive sampling. Multiple linear regression analysis was also for analyzing the data. The results showed that (1) there is a significant difference between the variables of brand image on brand loyalty Nike shoes in Surabaya, (2) there is also a significant difference between the variables of confidence in the brand to brand loyalty Nike shoes in Surabaya (3) a significant difference between the variables customer satisfaction on brand loyalty Nike shoes in Surabaya.